Mixed convective heat transfer enhancement in a ventilated cavity by flow modulation via rotating plate. Issue 3 (19th October 2020) - Islam, Aminul; Rony, Monoranjan Debnath; Islam, Mahmudul; Chowdhury, Emdadul Haque; Hasan, Mohammad Nasim
Abstract: The present study numerically explores the mixed convection phenomena in a differentially heated ventilated square cavity with active flow modulation via a rotating plate. Forced convection flow in the cavity is attained by maintaining external fluid flow through an opening at the bottom of the left cavity wall while leaving it through another opening at the right cavity wall. A counter‐clockwise rotating plate at the center of the cavity acts as an active flow modulator. Moving mesh approach is used for the rotation of the plate and the numerical solution is achieved using arbitrary Lagrangian‐Eulerian finite element formulation with a quadrilateral discretization scheme. Transient parametric simulations have been performed for various frequency of the rotating plate for a fixed Reynolds number ( Re ) of 100 based on maximum inlet flow velocity while the Richardson number ( Ri ) is maintained at unity. Heat transfer performance has been evaluated in terms of spatially averaged Nusselt number and time‐averaged Nusselt number along the heated wall. Power spectrum analysis in the frequency domain obtained from the fast Fourier transform analysis indicates that thermal frequency and plate frequency start to deviate from each other at higher values of velocity ratio (>4).